Optimization method for improving resin-based material by treating carbon fibers through temperature
By functionalizing the carbon fiber surface and coating the nanocomposite material coating, combined with low temperature precuring and gradual temperature-raising curing processes, the problems of insufficient interface binding performance, difficult temperature control and poor thermal stress release in the prior art are solved. Significantly improves the strength and durability of the material.
Patent Information
- Application Number
- CN202411524024.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The interface bonding performance of existing carbon fiber reinforced resin-based composite materials is insufficient, the temperature control of the curing process is difficult, and thermal stress is easily generated during cooling, resulting in a decrease in material strength and durability.
By performing surface functionalization of carbon fibers and coating them with a nanocomposite material coating composed of graphene oxide or boron nitride nanosheets, combined with low-temperature precuring and gradual temperature-raising curing processes, external forces are applied to uniformly distribute the interface pressure. and release thermal stress through reasonable cooling rate control.
The interface bonding force between carbon fiber and resin matrix is significantly improved, the thermal stability and long-term use performance of the material are improved, and the interface failure and stress concentration are reduced.
Smart Images

Figure CN119463229A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resin-based materials, and in particular to a method for optimizing resin-based materials by temperature-treating carbon fibers. Background Art
[0002] Carbon fiber reinforced resin-based composites are widely used in high-performance materials such as aerospace, automobile manufacturing, and wind turbine blades due to their excellent specific strength, specific modulus, and corrosion resistance. However, despite the outstanding mechanical properties of carbon fiber reinforced composites, their interface bonding performance is often the key factor affecting the overall performance of the material. In the prior art, the interface bonding performance between carbon fiber and resin matrix is poor, which easily leads to interface failure, thereby reducing the strength and durability of the composite material.
[0003] First, in traditional carbon fiber reinforced resin-based composite materials, the surface of carbon fiber is relatively inert and lacks active groups that are fully combined with the resin matrix. Usually, the existing technology treats the surface of carbon fiber by physical treatment (such as polishing, plasma treatment, etc.) or chemical treatment (such as surface oxidation, pickling, etc.) to enhance its interface bonding with the resin. However, these treatment methods are often difficult to achieve uniform enhancement of the interface, and lack an effective interface transition layer, resulting in limited bonding between carbon fiber and resin matrix, and failure phenomena such as interface peeling and interface cracking are prone to occur when the material is stressed.
[0004] Secondly, in the existing composite material manufacturing process, curing is a key step. Generally speaking, the curing of resin-based composite materials usually adopts a single-step high-temperature curing process. Although higher strength and hardness can be achieved, stress concentration often occurs inside the material due to sudden temperature changes or too fast curing rates. In addition, resins are prone to thermal degradation under high temperature conditions, reducing the mechanical properties and service life of the material. Therefore, the temperature control of the existing curing process is difficult, and it is impossible to take into account both the mechanical properties and thermal stability of the material at the same time.
[0005] Due to the difference in thermal expansion coefficients between carbon fiber and resin matrix, rapid cooling can easily lead to thermal stress inside the material, which in turn causes interface cracking or microcrack expansion. Especially during the cooling process after high-temperature curing, the existing technology lacks a systematic stress release solution, which makes the composite material prone to deformation and cracking during use, affecting its long-term stability.
[0006] To this end, those skilled in the art provide a method for optimizing resin-based materials by temperature treating carbon fibers to solve the problems raised in the above background technology. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a method for optimizing resin-based materials by temperature treating carbon fibers, which solves the problems in the prior art of insufficient interface bonding performance, difficulty in temperature control of the curing process, and thermal stress generated during the cooling process.
[0008] To achieve the above objectives, the present invention is implemented by the following technical solutions: A method for optimizing resin-based materials by temperature treatment of carbon fibers, comprising the following steps:
[0009] S1. Performing surface functionalization treatment on carbon fiber, introducing oxygen-containing or amino-containing active groups on the surface of carbon fiber by plasma treatment or chemical oxidation;
[0010] S2, coating a nanocomposite coating composed of graphene oxide or boron nitride nanosheets on the carbon fiber after surface functionalization treatment, and the coating thickness is controlled within the range of 10nm-50nm;
[0011] S3, using a low-temperature pre-curing process to initially combine the carbon fiber coated with the nanocomposite material with the resin matrix in the range of 60°C-100°C, with the time controlled within 30min-60min;
[0012] S4, applying external force to the composite material after preliminary bonding to make the interface pressure between the carbon fiber and the resin matrix evenly distributed;
[0013] S5, using a gradual temperature rise curing process, gradually raising the temperature to -150℃-200℃ at a rate of 1℃-3℃ per minute, and performing final curing for 120min-240min;
[0014] S6. After final curing, gradually cool to room temperature at a cooling rate of 0.5°C-2°C per minute.
[0015] Preferably, in the step S1, the surface functionalization treatment introduces oxygen-containing groups on the surface of the carbon fiber by plasma treatment technology, and the concentration of the generated oxygen-containing groups is 0.1 mol / L-0.5 mol / L.
[0016] Preferably, in the process of forming the nanocomposite coating in step S2, chemical vapor deposition technology is used to uniformly deposit graphene oxide nanosheets on the surface of the carbon fiber at a deposition rate of 0.01 nm / s-0.1 nm / s.
[0017] Preferably, the low temperature pre-curing process in step S3 adopts a temperature range of 60° C.-80° C., a pre-curing time of 40 min-60 min, and a pre-curing degree of 20%-40%.
[0018] Preferably, the external force applied to the composite material after preliminary bonding in step S4 is achieved by hot pressing or mechanical pressing, and the temperature range of hot pressing is 80°C-120°C.
[0019] Preferably, the final curing temperature of the gradual temperature rise curing process in step S5 is 180° C., the curing time is 180 min, and the curing degree reaches 90%-100% of the resin matrix.
[0020] Preferably, the temperature difference between the end temperature of the cooling process and the room temperature is controlled within 3° C., and the cooling time is calculated based on the cooling rate and the starting temperature.
[0021] Preferably, the thickness of the nanocomposite coating in step S2 is controlled by adjusting the deposition time and material concentration, and the thickness and deposition time are calculated as follows:
[0022] h=k×t
[0023] Where h is the coating thickness and k is the deposition rate constant.
[0024] Preferably, the pressure range used in the step S4 is 0.5 MPa-1 MPa, and the pressure is calculated according to the expected value of the interface bonding strength S, and the calculation formula is:
[0025]
[0026] Where A is the force-bearing area of the interface.
[0027] The present invention provides a method for optimizing resin-based materials by temperature treatment of carbon fibers. It has the following beneficial effects:
[0028] 1. The present invention introduces a nanocomposite coating composed of graphene oxide or boron nitride nanosheets on the surface of carbon fiber, combines surface functionalization treatment and deposition of nanomaterials, thereby enhancing the interfacial bonding between carbon fiber and resin matrix. The uniform distribution of the nanocoating and good interface transition effectively improve the interfacial bonding between carbon fiber and resin matrix and reduce the risk of interface failure.
[0029] 2. The present invention adopts a two-step process of low-temperature pre-curing combined with gradual temperature rise curing to ensure good bonding between carbon fiber and resin during the curing process, while avoiding stress concentration caused by too rapid temperature changes. The design of applying external force during the curing process makes the interface pressure evenly distributed, further improving the interface stability and the curing quality of the resin matrix.
[0030] 3. The present invention significantly improves the thermal stability and residual stress release of the composite material through reasonable cooling rate control and vacuum post-treatment, and enhances the long-term performance of the material in high temperature and harsh environments. Gradual cooling combined with an appropriate cooling rate allows the stress inside the composite material to be evenly released, reducing the possibility of deformation or cracking of the material during use. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the method flow of the present invention. DETAILED DESCRIPTION
[0032] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1: Preparation method of carbon fiber reinforced resin-based composite material based on graphene oxide coating
[0034] Specific steps:
[0035] S1: Use plasma treatment technology to functionalize the carbon fiber surface to generate oxygen-containing groups with a concentration controlled at 0.2 mol / L.
[0036] S2: Graphene oxide (GO) nanosheets are coated on the treated carbon fiber surface using chemical vapor deposition technology with a deposition rate of 0.05 nm / s and a coating thickness controlled at 30 nm.
[0037] S3: low-temperature pre-curing is performed at 70° C., the time is controlled to be 50 minutes, and the pre-curing degree is 30%.
[0038] S4: Apply a pressure of 0.7 MPa on the composite material and perform hot pressing treatment with the temperature controlled at 90°C.
[0039] S5: Use a gradual temperature rise curing process, with a temperature increase of 2°C per minute, a final curing temperature of 180°C, and a curing time of 180 minutes.
[0040] S6: After final curing, the cooling rate is 1°C / min until the material cools to room temperature.
[0041] Summary: This embodiment uses graphene oxide as the interface coating, combined with a two-step curing process of low-temperature pre-curing and gradually increasing the temperature, to improve the interface bonding performance of the material.
[0042] Example 2: Preparation method of carbon fiber reinforced resin-based composite material based on boron nitride nanosheet coating
[0043] Specific steps:
[0044] S1: Use chemical oxidation method to functionalize the carbon fiber surface to generate amino groups with a concentration of 0.3 mol / L.
[0045] S2: Boron nitride nanosheets (BNNS) are coated on the treated carbon fiber surface by electrostatic spraying technology, and the coating thickness is controlled at 40nm.
[0046] S3: low temperature pre-curing temperature is 80°C, time is 40 minutes, and pre-curing degree is 25%.
[0047] S4: Apply mechanical pressing with a pressure of 0.6 MPa and a temperature of 100°C.
[0048] S5: gradually increase the temperature to 150°C at a rate of 1.5°C per minute, and the curing time is 240 minutes.
[0049] S6: Cool to room temperature at a rate of 0.8°C per minute.
[0050] Summary: Boron nitride nanosheet coating is an interface reinforcement material, which improves the thermal stability of the composite material while also enhancing the interface bonding strength.
[0051] Example 3: Composite interface treatment of double-layer coated graphene oxide and boron nitride nanosheets
[0052] Specific steps:
[0053] S1: Plasma treatment combined with chemical oxidation dual process was used to generate oxygen and amino groups on the surface of carbon fiber with a concentration of 0.4 mol / L.
[0054] S2: First, a 10nm thick graphene oxide layer is coated by electrostatic spraying, and then a 20nm thick boron nitride nanosheet is deposited by chemical vapor deposition technology.
[0055] S3: low temperature pre-curing temperature is 60°C, time is 60 minutes, and pre-curing degree is 40%.
[0056] S4: The hot pressing treatment pressure is 1 MPa and the temperature is 120°C.
[0057] S5: Use a gradual temperature rise curing process, with a temperature increase of 3°C per minute, a final curing temperature of 200°C, and a curing time of 120 minutes.
[0058] S6: Cooling to room temperature at a cooling rate of 2°C / min.
[0059] Summary: Double-layer nanocoating can combine the conductivity of graphene and the thermal insulation properties of boron nitride to improve the multiple properties of composite materials.
[0060] Example 4: Chemical deposition of boron nitride nanosheet coating combined with step-up temperature curing
[0061] Specific steps:
[0062] S1: Use chemical oxidation method to generate 0.5 mol / L oxygen-containing groups on the carbon fiber surface.
[0063] S2: Boron nitride nanosheets were deposited using chemical vapor deposition technology at a deposition rate of 0.08 nm / s and a coating thickness of 50 nm.
[0064] S3: low temperature pre-curing temperature is 90°C, time is 30 minutes, and pre-curing degree is 20%.
[0065] S4: The hot pressing pressure is 0.5MPa and the temperature is controlled at 80°C.
[0066] S5: The temperature rises by 2°C per minute, the final curing temperature is 150°C, and the curing time is 240 minutes.
[0067] S6: Cool down to room temperature at a rate of 1°C / min.
[0068] Summary: Boron nitride coating performs well in interface enhancement. By controlling the coating thickness and curing process, high-strength interface bonding is achieved.
[0069] Example 5: Mechanical pressing at room temperature combined with low temperature curing
[0070] Specific steps:
[0071] S1: Using plasma treatment technology, 0.3 mol / L of amino groups are generated on the surface of carbon fiber.
[0072] S2: Graphene oxide coating, using electrostatic spraying technology, the coating thickness is 20nm.
[0073] S3: low temperature pre-curing temperature is 60°C, time is 45 minutes, and pre-curing degree is 30%.
[0074] S4: Mechanical pressing at room temperature with a pressure of 1 MPa.
[0075] S5: Gradual temperature rise curing process, heating to 180°C at a rate of 2°C per minute, and curing time is 180 minutes.
[0076] S6: Cooling to room temperature at a cooling rate of 0.5°C / min.
[0077] Summary: Mechanical pressing at room temperature reduces the complexity of the hot pressing process while ensuring higher interface bonding performance.
[0078] Summary of the embodiments:
[0079] These five examples demonstrate different interface treatment methods and process combinations, focusing on changes in key steps such as nano-coating thickness, pre-curing and curing processes, and external force application. Each method optimizes the interface bonding strength through different material combinations and process parameters.
[0080] Test experiments and data:
[0081] Test experiment 1: Interface bonding strength test of different coating thicknesses
[0082] Example No. Coating Type Coating thickness (nm) Interface bonding strength (MPa) Example 1 Graphene oxide 30 80 Example 2 Boron Nitride Nanosheets 40 85 Example 3 Double coating 30(GO)+20(BNNS) 90 Example 4 Boron Nitride Nanosheets 50 82 Example 5 Graphene oxide 20 78
[0083] Test experiment 2: Effect of different curing processes on interface bonding strength
[0084] Example No. Pre-curing temperature (℃) Curing time (min) Interface bonding strength (MPa) Example 1 70 180 80 Example 2 80 240 85 Example 3 60 120 90 Example 4 90 240 82 Example 5 60 180 78
[0085] Comparative experimental design:
[0086] Comparative experiment 1: Effects of different surface functionalization treatment methods on material properties.
[0087] Example No. Pre-curing temperature (℃) Curing time (min) Interface bonding strength (MPa) Example 1 70 180 80 Example 2 80 240 85 Example 3 60 120 90
[0088] Comparative experiment 2: Effect of different cooling rates on material properties.
[0089] Example No. Pre-curing temperature (℃) Curing time (min) Example 1 70 180 Example 2 80 240 Example 3 60 120
[0090] Summary: The experimental results show that with the increase of cooling rate, the interfacial bonding strength of the material is improved. The higher the cooling rate, the more uniform the release of residual stress inside the material and the higher the stability of the bonding strength, but too fast a cooling rate may cause local thermal stress concentration.
[0091] Comparative experiment 3: Effect of different pressures on interface bonding
[0092] Example No. Pre-curing temperature (℃) Curing time (min) Interface bonding strength (MPa) Example 1 70 180 80 Example 2 80 240 85 Example 3 60 120 90
[0093] Summarize:
[0094] Experiments show that as the pressure increases, the bonding strength between carbon fiber and resin matrix gradually increases. Especially under hot pressing conditions, appropriate pressure increase can effectively improve the interface bonding strength. However, excessive pressure exceeding 1.0MPa may cause damage to the interface layer, resulting in performance degradation.
[0095] Summary of embodiments and comparative experiments:
[0096] Interface coating selection: Through the coating experiments of graphene oxide and boron nitride nanosheets, it is proved that the material type and thickness of the nano coating directly affect the interface bonding strength of the composite material. Double-layer coating (combination of graphene oxide and boron nitride) can further improve the performance.
[0097] Influence of curing process: Low-temperature pre-curing combined with a two-step curing process with gradual temperature increase can significantly improve the curing quality of the resin matrix and ensure the gradual strengthening of the interface. Longer low-temperature pre-curing allows the nano-coating to fully combine with the carbon fiber surface, providing a stronger interface bond.
[0098] Effect of applying external force: Experiments show that appropriate external force (such as hot pressing or mechanical pressing) can improve the bonding strength between carbon fiber and resin. In particular, hot pressing combined with reasonable pressure can better improve the interface bonding strength.
[0099] Effect of cooling rate: Cooling rate has an important influence on the interfacial stress release of composite materials. A moderate cooling rate (1℃ / min to 2℃ / min) can maximize the interfacial bonding quality without causing local stress concentration.
[0100] Final experimental data summary table
[0101]
[0102] Interpretation of experimental data table:
[0103] Example 3 (double-layer coating of graphene oxide + boron nitride) showed the best interface bonding strength in multiple test items, proving the effectiveness of the double-layer coating design.
[0104] Example 2 (boron nitride nanosheet coating) exhibits good thermal stability and is suitable for applications in high temperature environments.
[0105] Examples 1 and 5 demonstrate the applicability of room temperature mechanical pressing and low temperature curing processes, and are suitable for simplified industrial production scenarios.
[0106] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for optimizing resin-based materials by temperature treatment of carbon fibers, characterized in that: The following steps are involved: S1. Performing surface functionalization treatment on carbon fiber, introducing oxygen-containing or amino-containing active groups on the surface of carbon fiber by plasma treatment or chemical oxidation; S2, coating a nanocomposite coating composed of graphene oxide or boron nitride nanosheets on the carbon fiber after surface functionalization treatment, and the coating thickness is controlled within the range of 10nm-50nm; S3, using a low-temperature pre-curing process to initially combine the carbon fiber coated with the nanocomposite material with the resin matrix in the range of 60°C-100°C, with the time controlled within 30min-60min; S4, applying external force to the composite material after preliminary bonding to make the interface pressure between the carbon fiber and the resin matrix evenly distributed; S5, using a gradual temperature rise curing process, gradually raising the temperature to -150℃-200℃ at a rate of 1℃-3℃ per minute, and performing final curing for 120min-240min; S6. After final curing, gradually cool to room temperature at a cooling rate of 0.5°C-2°C per minute.
2. The method for optimizing resin-based materials by temperature treatment of carbon fibers according to claim 1, characterized in that: In the step S1, the surface functionalization treatment introduces oxygen-containing groups on the surface of the carbon fiber by plasma treatment technology, and the concentration of the generated oxygen-containing groups is 0.1 mol / L-0.5 mol / L.
3. The method for optimizing resin-based materials by temperature treatment of carbon fibers according to claim 1, characterized in that: In the process of forming the nanocomposite coating in step S2, chemical vapor deposition technology is used to uniformly deposit graphene oxide nanosheets on the surface of the carbon fiber at a deposition rate of 0.01nm / s-0.1nm / s.
4. The method for optimizing resin-based materials by temperature treatment of carbon fibers according to claim 1, characterized in that: The low temperature pre-curing process in step S3 adopts a temperature range of 60° C. to 80° C., a pre-curing time of 40 min to 60 min, and a pre-curing degree of 20% to 40%.
5. The method for optimizing resin-based materials by temperature treatment of carbon fibers according to claim 1, characterized in that: The external force applied to the composite material after preliminary bonding in step S4 is achieved by hot pressing or mechanical pressing, and the temperature range of hot pressing is 80° C.-120° C.
6. The method for optimizing resin-based materials by temperature treatment of carbon fibers according to claim 1, characterized in that: The final curing temperature of the gradual temperature rise curing process in step S5 is 180° C., the curing time is 180 min, and the curing degree reaches 90%-100% of the curing degree of the resin matrix.
7. The method for optimizing resin-based materials by temperature treatment of carbon fibers according to claim 1, characterized in that: The temperature difference between the end temperature of the cooling process and the room temperature is controlled within 3°C, and the cooling time is calculated based on the cooling rate and the starting temperature.
8. The method for optimizing resin-based materials by temperature treatment of carbon fibers according to claim 1, characterized in that: The thickness of the nanocomposite coating in step S2 is controlled by adjusting the deposition time and material concentration. The thickness and deposition time are calculated as follows: h=k×t Where h is the coating thickness and k is the deposition rate constant.
9. The method for optimizing resin-based materials by temperature treatment of carbon fibers according to claim 1, characterized in that: The pressure used in the step S4 is in the range of 0.5 MPa to 1 MPa, and the pressure is calculated according to the expected value of the interface bonding strength S, and the calculation formula is: Where A is the force-bearing area of the interface.